My view of the Nepal Administrative Staff College - Tuladhar, Subarna Man (Administration and Management Review, 2008)
The best way to improve the performance of an organisation is to train its people. Major countries and many smaller ones throughout the world have equipped themselves with Administrative Staff College to train public servants. This paper introduces the Nepal Administrative Staff College (NASC), outlines the historical background to its establishment, features information about its past twenty-five years, describes its current activities, and hopes for its future development. Dear readers will find it not only useful but helfpful in figuring out what NASC is all about.Administration and Management Review Vol.19, No. 2, Special Issue(2007) pp. 17-46